Band Offset Measurements in Atomic-Layer-Deposited Al2O3/Zn0.8Al0.2O Heterojunction Studied by X-ray Photoelectron Spectroscopy - Baojun Yan; Shulin Liu; Yuekun Heng; Yuzhen Yang; Yang Yu; Kaile Wen (Nanoscale Research Letters, 2017)
Abstract Pure aluminum oxide (Al2O3) and zinc aluminum oxide (Zn x Al1-x O) thin films were deposited by atomic layer deposition (ALD). The microstructure and optical band gaps (E g ) of the Zn x Al1-x O (0.2 ≤ x ≤ 1) films were studied by X-ray diffractometer and Tauc method. The band offsets and alignment of atomic-layer-deposited Al2O3/Zn0.8Al0.2O heterojunction were investigated in detail using charge-corrected X-ray photoelectron spectroscopy. In this work, different methodologies were adopted to recover the actual position of the core levels in insulator materials which were easily affected by differential charging phenomena. Valence band offset (ΔE V) and conduction band offset (ΔE C) for the interface of the Al2O3/Zn0.8Al0.2O heterojunction have been constructed. An accurate value of ΔE V = 0.82 ± 0.12 eV was obtained from various combinations of core levels of heterojunction with varied Al2O3 thickness. Given the experimental E g of 6.8 eV for Al2O3 and 5.29 eV for Zn0.8Al0.2O, a type-I heterojunction with a ΔE C of 0.69 ± 0.12 eV was found. The precise determination of the band alignment of Al2O3/Zn0.8Al0.2O heterojunction is of particular importance for gaining insight to the design of various electronic devices based on such heterointerface.